Aspectos da autonomia culinária de universitários antes e durante a pandemia de COVID-19 - Beatriz Almeida Machado; Marina Muniz Aguiar; Camilla Medeiros Macedo da Rocha; Caroline Ferreira Soares Cabral; Carla Adriano Martins; Mariana Fernandes Brito de Oliveira (Universidade do Estado do Rio de Janeiro, 2022)
Introduction: The pandemic resulting from the spread of coronavirus (Covid-19) forced countries to implement strict health policies, including social isolation measures. Objective: This original study evaluated aspects of the culinary autonomy of university students before and during the social isolation resulting from the Covid-19 pandemic. Method: A descriptive cross-sectional study was developed, and conducted between June and July 2020, with the application of an online questionnaire focussing on aspects of culinary autonomy before and during isolation for comparison and evaluation, as well as socio-demographic data. The association between the variables of interest was assessed using Pearson's chi-square test. Results: 233 university students participated in the research, most of them female (71.2%) and aged between 20 and 25 years (74.6%). During the isolation period, the frequency with which these students cooked increased, as did their use of a pressure cooker (an indicator of confidence in the kitchen), the division of tasks in the kitchen and the consumption of natural or minimally processed foods, although access and going to street markets decreased. Conclusion: Among the participants, the period of isolation seems to have contributed, at an individual level, to the development of culinary autonomy. Whether in times of a pandemic or not, this development is necessary for people to create ways to economize and to prepare their own meals. The findings therefore contribute to the dialogue on the promotion of health and quality of life through home cooking.